2013
DOI: 10.1088/0967-3334/34/10/1217
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic impedance spectra identification from time-varying bioimpedance: theory and validation

Abstract: The harmonic impedance spectra (HIS) of a time-varying bioimpedance Z(ω, t) is a new tool to better understand and describe complex time-varying biological systems with a distinctive periodic character as, for example, cardiovascular and respiratory systems. In this paper, the relationship between the experimental setup and the identification framework for estimating Z(ω, t) is set up. The theory developed applies to frequency response based impedance measurements from noisy current-voltage observations. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…In fact, we initially also identified a similar finding. However, a close look at our data revealed that this perception was due to the temporal window T w needed to discretize data to compute the impedance frequency response using the short time Fourier transform (STFT) [16]. To further prove this, we show Figure 9.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In fact, we initially also identified a similar finding. However, a close look at our data revealed that this perception was due to the temporal window T w needed to discretize data to compute the impedance frequency response using the short time Fourier transform (STFT) [16]. To further prove this, we show Figure 9.…”
Section: Discussionmentioning
confidence: 83%
“…The muscle impedance was measured using a custom broadband impedance frequency response analyzer (FRA) [12], [15], [16]. The impedance measurement system was implemented on a rugged PC-platform PXI (PCI eXtensions for Instrumentation) platform from National Instruments.…”
Section: E Impedance Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance was calculated on the basis of the division of the output-input Fast Fourier Transform (FFT) coefficients at the excited frequencies [38]. Once the impedance was calculated, noise reduction was performed with a moving average filter (length n=10) independently for each 860 ms continuous measurement segment.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…based on multisines signals [10], [11], [12]. Using the multifrequency approach, many frequencies are applied simultaneously (B) and the time to acquire a complete EIM spectrum is drastically reduced making it possible to measure the instantaneous impedance changes and temporal evolution of dynamic EIM, for example, during muscle contraction and relaxation and to collect both nonand fatigued muscle data.…”
Section: Impedance Instrumentationmentioning
confidence: 99%